International students’ university choice to study abroad in higher education and influencing factors analysis - Ke, Hu; Junfeng, Diao; Xiaojing, Li (Frontiers in Psychology, 2022)
Abstract：With the development of China’s higher education, China has become increasingly popular as an education destination for international students. To explore the rationale and the influencing factors for them to attend Chinese universities, this research adopted a questionnaire survey and interviews with international students from a top university in China. The data were analyzed from four aspects: home countries’ push factors, China’s pull factors, university attractiveness factors and personal choice factors. The findings show that university attractiveness factors are more significant than the China’s pull factors and the home countries push factors; China’s pull factors have significant influence on the university attractiveness factors; For students from different regions, the factors of China’s pull, home country’s push and university attractiveness play significantly different role in affecting their choice of university, with Asian students much more affected than those from other parts of the world. Besides, individual subjective norms and individual value choices also affect students’ choices to study abroad.